Pemulihan Fisik dan Emosi serta Reintegrasi ke Masyarakat Sebagai Program Rehabilitasi Sosial Utama bagi Narapidana Narkotika di Lembaga Pemasyarakatan - Rahmadani, Rosy Putri; Kusmiyanti, Kusmiyanti (FORIKES, 2025)
Drug abuse in Indonesia is a crucial issue because it directly impacts the high number of drug convicts in correctional institutions. The purpose of this study was to examine the role and barriers to social rehabilitation for drug convicts. This study was a systematic literature review conducted over a five-month period. Scientific articles were obtained from several database. Article selection was based on inclusion and exclusion criteria, and used the PICO (Population, Intervention, Comparison, Outcome) framework to focus the search. A total of 200 articles were obtained, which were then extracted and analyzed using a thematic analysis approach to identify patterns, common threads, and categories of findings. The study results indicated eight main roles of social rehabilitation: physical and emotional recovery, social skills development, self-potential enhancement, social reintegration, dependency reduction, motivation enhancement, security and order enhancement in prisons, and behavioral change. In addition, various barriers were identified, such as the absence of specialized programs, shortage of experts, limited facilities and infrastructure, overcapacity, weak social support, overlapping regulations, cultural and operational challenges, and maladaptive behavior. It can be concluded that the success of social rehabilitation programs depends heavily on integrated policy design, cross-sectoral support, and a comprehensive and sustainable approach. Keywords: social rehabilitation; drug convicts; correctional institutions ABSTRAK Penyalahgunaan narkotika di Indonesia menjadi isu krusial karena berdampak langsung terhadap tingginya jumlah narapidana narkotika di lembaga pemasyarakatan. Tujuan studi ini adalah mengkaji peran dan hambatan rehabilitasi sosial bagi narapidana narkotika. Studi ini merupakan systematic literature review yang dilakukan selama 5 bulan. Artikel ilmiah diperoleh dari beberapa database. Seleksi artikel dilakukan berdasarkan kriteria inklusi dan eksklusi, serta menggunakan kerangka PICO (Population, Intervention, Comparison, Outcome) untuk memfokuskan pencarian. Sebanyak 200 artikel didapatkan, yang selanjutnya diekstraksi dan dianalisis menggunakan pendekatan analisis tematik untuk mengidentifikasi pola, benang merah, serta kategori temuan. Hasil studi menunjukkan bahwa terdapat delapan peran utama dari rehabilitasi sosial, yaitu pemulihan fisik dan emosional, pengembangan keterampilan sosial, peningkatan potensi diri, reintegrasi sosial, pengurangan ketergantungan, peningkatan motivasi, peningkatan keamanan dan ketertiban di lapas, serta perubahan perilaku. Selain itu, ditemukan berbagai hambatan seperti ketiadaan program khusus, kekurangan tenaga ahli, keterbatasan sarana dan prasarana, overkapasitas, lemahnya dukungan sosial, tumpang tindih regulasi, tantangan budaya dan operasional, serta perilaku maladaptif. Dapat disimpulkan bahwa keberhasilan program rehabilitasi sosial sangat bergantung pada desain kebijakan yang terintegrasi, dukungan lintas sektor, serta pendekatan yang bersifat menyeluruh dan berkelanjutan. Kata kunci: rehabilitasi sosial; narapidana narkotika; lembaga pemasyarakatan